A new biomechanical FE model for blunt thoracic impact - Chaufer, Martin; Delille, Rémi; Bourel, Benjamin; Marechal, Christophe; Lauro, Franck; Mauzac, Olivier; Roth, Sebastien (Frontiers in Bioengineering and Biotechnology, 2023)
In the field of biomechanics, numerical procedures can be used to help understand complex phenomena that cannot be analyzed with experimental setups. The use of experimental data from human cadavers can present ethical issues, which can be avoided by utilizing biofidelic models. Biofidelic models have been demonstrated to have wide-ranging benefits, particularly in evaluating the effectiveness of protective devices such as body armor. For instance, numerical twins coupled with a biomechanical model can be used to assess the efficacy of protective devices against intense external forces. Similarly, the use of human body surrogates in experimental studies has allowed for biomechanical studies, as demonstrated by the development of crash test dummies that are commonly used in automotive crashworthiness testing. This study proposes using numerical procedures and simplifying the structure of an existing biofidelic FE model of the human thorax as a preliminary step in building a physical surrogate. A reverse engineering method was used to ensure the use of manufacturable materials, which resulted in a FE model called SurHUByx FEM (Surrogate HUByx Finite Element Model, with HUByx being the initial thorax FE model developed previously). This new simplified model was validated against existing experimental data on cadavers in the context of ballistic impact. SurHUByx FEM, with its new material properties of manufacturable materials, demonstrated consistent behavior with biomechanical corridors derived from these experiments. The validation process of this new simplified FE model yielded satisfying results and is the first step towards the development of its physical twin using manufacturable materials.